2022
DOI: 10.3390/children9060923
|View full text |Cite
|
Sign up to set email alerts
|

Externalizing and Internalizing Behaviors in Children with ADHD during Lockdown for COVID-19: The Role of Parental Emotions, Parenting Strategies, and Breaking Lockdown Rules

Abstract: Lockdown experience for COVID-19 pandemic significantly affected children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD) exacerbating or promoting the onset of externalizing and internalizing symptoms. However, few studies have considered how externalizing and internalizing behaviors changed in relation to parental emotions and parenting strategies. In the present study, 992 caregivers of children and adolescents with ADHD from 5 to 18 years were presented with an online survey evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…On the other hand, the urgency of caring and rearing children with NDD without the usual external support may have led to overwhelm and increased parental stress, which in turn may have biased the judgement of children's externalizing behaviors. However, independently from the reasons why the externalizing behaviors were perceived as worsened, it is important to carefully consider the parents' perceptions, as there is a well-documented reciprocal influence between the severity of child behavioral difficulties and caregiver burden [20,56,57]. Our results corroborate this relation.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, the urgency of caring and rearing children with NDD without the usual external support may have led to overwhelm and increased parental stress, which in turn may have biased the judgement of children's externalizing behaviors. However, independently from the reasons why the externalizing behaviors were perceived as worsened, it is important to carefully consider the parents' perceptions, as there is a well-documented reciprocal influence between the severity of child behavioral difficulties and caregiver burden [20,56,57]. Our results corroborate this relation.…”
Section: Discussionsupporting
confidence: 78%
“…Again, children with internalizing behaviors resulted susceptible to remission of some sleep problems; conversely, this did not happen with children with externalizing behaviors. Studies on patients with ADHD during lockdown reported significantly increased disruptive behaviors in around 50% of them, and altered child/parents interaction characterized by marked increase in irritability, shouts and verbal abuse, and punishments [ 19 , 22 , 32 , 33 ]. Altogether the results suggest that sleep problems could contribute to exacerbate or promote the externalizing behaviors considering that, other studies highlighted a positive association with the externalizing behaviors but not with the internalizing ones [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on patients with ADHD during lockdown reported significantly increased disruptive behaviors in around 50% of them, and altered child/parents interaction characterized by marked increase in irritability, shouts and verbal abuse, and punishments [ 19 , 22 , 32 , 33 ]. Altogether the results suggest that sleep problems could contribute to exacerbate or promote the externalizing behaviors considering that, other studies highlighted a positive association with the externalizing behaviors but not with the internalizing ones [ 33 ]. Conversely, the hypothesis of a bidirectional relationship between some sleep problems and internalizing symptoms reported in recent studies seems also to be supported [ 5 ].…”
Section: Discussionmentioning
confidence: 99%